Democracy or Bonapartism two centuries of war on democracy - Losurdo, Domenico 1941-2018 (Verso, 2024)
"How an iron fist donned democracy's velvet glove. The history of universal suffrage is best understood as a conflict between liberal elites and democratic workers' movements, according to Domenico Losurdo. John Stuart Mill, for example, argued that electoral influence should be more pronounced among the educated -- and wealthy -- than among those working with their hands. Every vote ought not to be counted the same. Countries with deep liberal roots have historically been quick to restrain the spread of the franchise, persisting in discrimination based on property, race, and gender. In this context, the rise of popular presidents and premiers, vested with extraordinary powers, has served to stimy attempts to associate politically and mobilize for meaningful change. This is modern Bonapartism, a soft authoritarianism in which popularity, stirred up by a news media dominated by the interests of the rich, replaces true democratic expression. As alternatives to this system drift toward the horizon, Bonapartism is set to become the dominant political regime of our era. Understanding the history of its development and the contradictory forces behind it may permit us to move towards true democracy."--
"First published as 'Democrazia o bonapartismo. Trionfo e decadenza del suffragio universale', © Bollati Boringhieri, 1993"--Title page verso
Keywords: Geschichte; Wahlrecht; Bonapartismus; Demokratie; Legitimation; Suffrage / History; Representative government and representation / History; Bonapartism / History; Suffrage / Histoire; Gouvernement représentatif / Histoire; Bonapartisme / Histoire; Bonapartism; Representative government and representation; Suffrage; History